Productivity Improvement Strategy: The Role Of Motivation And Work Experience In Kusno Raharjo Public Appraisal Services Office - Nita Kanya; Windy Widiaswara; Ahmad Johan (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
Purpose: The purrpose of this research was to determinate the influence motivation and work experience on the work productivity at Kantor Jasa Penilai Publik Kusno Raharjo. Method: The method used is descriptive and verification analysis. The data collection technique used is literature study and distributed questionnaries with 30 respondents. The analysis using SPSS 26.0 SoftwareResult: Summarize the result or findings of your study. Practical Implications for Economic Growth and Development: Based on the result of this research, motivation and work experience on the work productivity at Kantor Jasa Penilai Publik Kusno Raharjo decision was very good. That both motivation and work experience have significant impact on the work productivity.